Radiative Parameters for Odd-parity Levels of V ii - Huiting Ma; Huifang Li; Hongfeng Zheng; Meina Liu; Zhenwen Dai (The Astrophysical Journal Supplement Series)
Experimental radiative lifetimes for 27 odd-parity levels of singly ionized vanadium (V ii ) ranging in energy from 34,592 to 62,286 cm ^−1 are measured by the time-resolved laser-induced fluorescence technique, and the lifetime results of 23 of these levels are reported for the first time as far as we know. Branching fractions are also determined using the downloaded archival spectral data recorded by the Fourier transform spectrometer at the National Solar Observatory on Kitt Peak, USA ( https://nso.edu/data/historical-archive/ ). And then transition probabilities and oscillator strengths of 107 transitions concerning 24 levels are derived by combining these lifetime and branching fraction results. The obtained results are compared with previously reported results available in the literature.